Diverse susceptibilities and responses of human and rodent cells to orthohantavirus infection reveal different levels of cellular restriction - Gallo, Giulia; Kotlik, Petr; Roingeard, Philippe; Monot, Marc; Chevreux, Guillaume; Ulrich, Rainer G; Tordo, Noël; Ermonval, Myriam (PLoS neglected tropical diseases, 2022)
Orthohantaviruses are rodent-borne emerging viruses that may cause severe diseases in humans but no apparent pathology in their small mammal reservoirs. However, the mechanisms leading to tolerance or pathogenicity in humans and persistence in rodent reservoirs are poorly understood, as is the manner in which they spread within and between organisms. Here, we used a range of cellular and molecular approaches to investigate the interactions of three different orthohantaviruses-Puumala virus (PUUV), responsible for a mild to moderate form of hemorrhagic fever with renal syndrome in humans, Tula virus (TULV) with low pathogenicity, and non-pathogenic Prospect Hill virus (PHV)-with human and rodent host cell lines. Besides the fact that cell susceptibility to virus infection was shown to depend on the cell type and virus strain, the three orthohantaviruses were able to infect Vero E6 and HuH7 human cells, but only the former secreted infectious particles. In cells derived from PUUV reservoir, the bank vole (Myodes glareolus), PUUV achieved a complete viral cycle, while TULV did not enter the cells and PHV infected them but did not produce infectious particles, reflecting differences in host specificity. A search for mature virions by electron microscopy (EM) revealed that TULV assembly occurred in part at the plasma membrane, whereas PHV particles were trapped in autophagic vacuoles in cells of the heterologous rodent host. We described differential interactions of orthohantaviruses with cellular factors, as supported by the cellular distribution of viral nucleocapsid protein with cell compartments, and proteomics identification of cellular partners. Our results also showed that interferon (IFN) dependent gene expression was regulated in a cell and virus species dependent manner. Overall, our study highlighted the complexity of the host-virus relationship and demonstrated that orthohantaviruses are restricted at different levels of the viral cycle. In addition, the study opens new avenues to further investigate how these viruses differ in their interactions with cells to evade innate immunity and how it depends on tissue type and host species.
Keywords: Interferons; viry; nukleokapsida - proteiny; Hantavirus; RNA-viry; Arvicolinae; Puumala virus; interferony; Rodentia; zvířata; Humans; hlodavci; Nucleocapsid Proteins; RNA Viruses; virus Puumala; Orthohantavirus; Viruses; lidé; Animals